STUDENTS’ PERCEPTIONS TOWARDS ENGLISH SPEAKING ABILITY - Musyrifah Mahfuddin; Budiarti Putri Uleng; Nasruddin Nasruddin (Jurnal Andi Djemma | Jurnal Pendidikan, 2024)
The aim of this research is to identify students’ perception toward English speaking ability. This research used descriptive qualitative research as the method. The observation and interview were used as the instrument. To increase the validity of the data, field note was used to support the methodology of the research. The result of this research found that the students’ perception towards English speaking ability is various. They realized that speaking is an important skill in English to be matered well. They argued that speaking is important skill to communicate each other especially as the International and global language used in the world. Most of them could not speak English well and fluently, and many students also considered that speaking is difficult to be mastered because of some aspects such as limited vocabulary, less understanding of grammar and also the pronounciation which cannot be practiced.